Delivery of Functional Anti-miR-9 by Mesenchymal Stem Cell-derived Exosomes to Glioblastoma Multiforme Cells Conferred Chemosensitivity - Jessian L Munoz; Sarah A Bliss; Steven J Greco; Shakti H Ramkissoon; Keith L Ligon; Pranela Rameshwar (Elsevier, 2013)
Glioblastoma multiforme (GBM), the most common and lethal tumor of the adult brain, generally shows chemo- and radioresistance. MicroRNAs (miRs) regulate physiological processes, such as resistance of GBM cells to temozolomide (TMZ). Although miRs are attractive targets for cancer therapeutics, the effectiveness of this approach requires targeted delivery. Mesenchymal stem cells (MSCs) can migrate to the sites of cancers, including GBM. We report on an increase in miR-9 in TMZ-resistant GBM cells. miR-9 was involved in the expression of the drug efflux transporter, P-glycoprotein. To block miR-9, methods were developed with Cy5-tagged anti-miR-9. Dye-transfer studies indicated intracellular communication between GBM cells and MSCs. This occurred by gap junctional intercellular communication and the release of microvesicles. In both cases, anti-miR-9 was transferred from MSCs to GBM cells. However, the major form of transfer occurred with the microvesicles. The delivery of anti-miR-9 to the resistant GBM cells reversed the expression of the multidrug transporter and sensitized the GBM cells to TMZ, as shown by increased cell death and caspase activity. The data showed a potential role for MSCs in the functional delivery of synthetic anti-miR-9 to reverse the chemoresistance of GBM cells.